2003
DOI: 10.1021/jf0343128
|View full text |Cite
|
Sign up to set email alerts
|

Processing of Sorghum (Sorghum bicolor) and Sorghum Products Alters Procyanidin Oligomer and Polymer Distribution and Content

Abstract: Sorghum procyanidins were characterized and quantified from two brown sorghum varieties and their processed products by normal phase HPLC with fluorescence detection. The DP of the procyanidins was determined by thiolysis. Quantification was done by using purified oligomeric and polymeric cocoa procyanidins as external standards. Sorghum procyanidins were composed mostly of high MW (DP > 10) polymers. Significant differences were observed in levels as well as distribution of the different MW procyanidins betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
88
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 142 publications
(96 citation statements)
references
References 27 publications
7
88
0
1
Order By: Relevance
“…Extrusion of sorghum grains resulted in an increase in the levels of procyanidin oligomers (DPa/ = 4) and a decrease in polymers (DPA/ = 6), possibly due to breakdown of the high-molecularweight polymers into lower-weight compounds. It was concluded that processing changed the overall procyanidin content in sorghum, and also the relative ratios of the different molecular weights [113].…”
Section: Effects On Tannins During Processingmentioning
confidence: 99%
“…Extrusion of sorghum grains resulted in an increase in the levels of procyanidin oligomers (DPa/ = 4) and a decrease in polymers (DPA/ = 6), possibly due to breakdown of the high-molecularweight polymers into lower-weight compounds. It was concluded that processing changed the overall procyanidin content in sorghum, and also the relative ratios of the different molecular weights [113].…”
Section: Effects On Tannins During Processingmentioning
confidence: 99%
“…Phenolic compounds appear to be susceptible to processing and extrusion has been shown to reduce the molecular weight of phenolic polymers in sorghum [58]. More recently, Dlamini, et al [59] reported that extrusion reduced average total phenol contents by 51% (14.92 versus 7.37 mg catechin equivalents/g) in the whole grain of five sorghum varieties.…”
Section: "Non-tannin" Polyphenolic Compounds and Phenolic Acidsmentioning
confidence: 99%
“…Tannin was extracted as described by Awika, Dykes, Gu, Rooney & Prior (2003), with slight modifications. One g sample was extracted in 10 mL acetone/acetic acid/water (70:1:29, v/v).…”
Section: Normal Phase High Performance Liquid Chromatography (Hplc)mentioning
confidence: 99%